If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -8) = 0 Reorder the terms: 4(-8 + x) = 0 (-8 * 4 + x * 4) = 0 (-32 + 4x) = 0 Solving -32 + 4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '32' to each side of the equation. -32 + 32 + 4x = 0 + 32 Combine like terms: -32 + 32 = 0 0 + 4x = 0 + 32 4x = 0 + 32 Combine like terms: 0 + 32 = 32 4x = 32 Divide each side by '4'. x = 8 Simplifying x = 8
| 22=t | | 8+1.25=16.75 | | 3x+38=16+x | | 184+2h=986 | | x+3x-1+x+15= | | 3x^2-6x+11000=0 | | 4x(x)=49 | | 2x^6*x-95=0 | | 0.2p-10= | | 6-4x=x+7(x+8) | | 144=16t | | 28(p+30)=3,108 | | 8.32+7.76-10.09= | | 3,108=28(p+30) | | x+(3x+4)=112 | | 6(2x-3)=24 | | X+(x-21)=157 | | 2x+12+7x-1=x | | 2(3x+3)=11x+3-5x+3 | | z/(-1)=9 | | -8+x=46 | | X+X-21=157 | | 6.8/(-4)= | | 2x+11x=52+x | | x-(-5)=34 | | 9x+15=5x+1 | | 4*(-4.3)*-2= | | X^2-15x-11000=0 | | 4(x+8)=8x+3-4x+29 | | 4b+3-b=-7+2+b | | 6-3(4x+2)-10x= | | (-X+1)2+(-x-1)2=0 |